Theoretical Studies of Rare-Earth Nuclei Leading to 50Sn-Daughter Products and the Associated Shell Effects - Kumar, S. (Ukrainian Journal of Physics, 2012)
Cluster decays of rare-earth nuclei are studied with regard for neutron magic shells for 50Sn nucleus as a daughter product always. The 100Sn and 132Sn radioactivities are studied to find the most probable cluster decays and the possibility, if any, of new neutron shells. For a wide range of parent nuclei considered here (from Ba to Pt), 12C and 78Ni from the 112Ba and 210Pt parents, respectively, are predicted to be the most probable clusters (minimum decay half-life) referring to100Sn and 132Sn daughters. The 22Mg decay of 122Sm is indicated at the second best possibilty for the 100Sn-daughter decay. In addition to these well-known magic shells (Z = 50, N = 50 and 82), a new magic shell at Z = 50, N = 66 (116Sn daughter) is indicated for the 64Ni decay from the 180Pt parent.